2000
DOI: 10.1177/019262330002800306
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Basis for Nonlinearities and Thresholds in Rat Liver Carcinogenesis by the DNA-Reactive Carcinogens 2-Acetylaminofluorene and Diethylnitrosamine

Abstract: To explore differences in mechanisms of carcinogenicity at low and high exposures, we have conducted a series of exposureresponse studies of hepatocarcinogenesis in rats using 2 well-studied DNA-reactive carcinogens, 2-acetylaminofluorene and diethylnitrosamine. In these studies, we have used intraperitoneal injection or intragastric instillation to deliver exact doses during an initiation segment followed by phenobarbital as a liver tumor promoter to enhance manifestation of initiation. This protocol results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 45 publications
5
63
1
1
Order By: Relevance
“…with DNA-reactive agents, as shown for a variety of tissues (Butterworth et al, 1992;Cunningham, 2000;Williams et al, 2000).…”
Section: Introductionmentioning
confidence: 83%
“…with DNA-reactive agents, as shown for a variety of tissues (Butterworth et al, 1992;Cunningham, 2000;Williams et al, 2000).…”
Section: Introductionmentioning
confidence: 83%
“…As Williams et al 50 reported that the cytotoxicity caused by injection of DEN is dose-dependent, we first performed doseresponse experiments to investigate if the loss of gp130 in hepatocytes might have a role in tumor initiation and progression. We have previously shown that the lack of gp130 promotes susceptibility to LPS-induced acute liver injury.…”
Section: 43mentioning
confidence: 99%
“…2-acetlaminofluorene Williams et al, 2000;Littlefield et al, 1980); dimethylnitrosamine (Peto et al, 1991); dibenzo[a,l]pyrene (Bailey et al, 2009); diethylnitrosamine (Peto et al, 1991;Williams et al, 2000)), it is still not possible to determine the nature of the relationship at human relevant exposures with confidence. For less studied chemicals, the lack of key evidence needed to make educated judgments about probable doseresponse curves (i.e.…”
Section: Page 16 Of 48mentioning
confidence: 99%